Position sensorless startup for doubly salient electro‐magnetic motor with only one test pulse. Issue 8 (20th June 2017) - Zhou, Xingwei; Zhou, Bo; Yang, Lan; Shi, Liwei
Abstract : The self‐inductance of doubly salient electro‐magnetic motor (DSEM) varies with rotor position, so it's becoming an effective approach to estimate rotor position in DSEM sensorless drive system. Based on the feature that there must be a change in the magnitude relation of two phase self‐inductances when the rotor goes from one sector to the other, this study proposes a novel rotor position estimation method for DSEM sensorless startup, it needs only one test pulse injection. The proposed method starts with injecting a test voltage pulse in all three‐phase windings by turning on three proper transistors a certain time synchronously. Then at the end of the test pulse, the response currents of the two parallel‐connected phases are sampled and compared for judging whether the rotor has reached the commutation instant. Moreover, the rotor position estimation error and output torque of the pulse‐injection‐based methods are theoretically analysed. Compared with the conventional rotor position estimating method which requires multiple test pulses, the proposed strategy has merits of less test time consuming, higher‐accurate commutation, greater output torque and superior startup performance. Finally, the experiments on a 12/8‐pole DSEM confirm the correctness and flexibility of the proposed method.